2001
DOI: 10.1677/erc.0.0080071
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac metastasis from primary anaplastic thyroid carcinoma: report of three cases and a review of the literature.

Abstract: Background: Clinically evident cardiac metastases from malignant neoplasms are uncommon. The frequency of thyroid metastasis to the heart is very low. To our knowledge, over the last 20 years only a few cases have been reported in the entire literature. Metastatic cardiac involvement occurs most often during the terminal stage. Patients: We present three cases of anaplastic thyroid cancer with metastatic involvement of the heart. Results: Two of the patients died from cardiac problems. The absence of early sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Intracardiac metastases are reported from several different primary cancers, including melanoma, bladder[4], sarcoma[5], lung, lymphoma, breast carcinoma[6] and cervix [7]. Cardiac metastases from primary anaplastic thyroid carcinoma are rare - an autopsy series has reported the rate as 0 to 2% [2]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Intracardiac metastases are reported from several different primary cancers, including melanoma, bladder[4], sarcoma[5], lung, lymphoma, breast carcinoma[6] and cervix [7]. Cardiac metastases from primary anaplastic thyroid carcinoma are rare - an autopsy series has reported the rate as 0 to 2% [2]. …”
Section: Discussionmentioning
confidence: 99%
“…Different routes of cancer spread have been reported, and include hematogenous, lymphatic, and direct extension to the heart or thoracic duct [2,8]. Retrograde lymphatic spread is predominant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, after a comprehensive literature review, we found only 15 case reports in the last 35 years [3, 4]. Thyroid cancer histologic subtypes more prone to develop cardiac metastases are anaplastic thyroid cancer, follicular thyroid cancer, and Hürthle cell cancer.…”
Section: Introductionmentioning
confidence: 99%